The Relationship Between Healthy Lifestyle Beliefs and Hygiene Behaviors of Adolescents During the COVID-19 Pandemic Process - Semra Kose; Arzu Sarialioglu; Gulsun Ayran (Galician Medical Journal, 2023)
Aim. The research was carried out to determine the relationship between healthy lifestyle beliefs and hygiene behaviors of adolescents during the COVID 19 pandemic process.